Perilous pursuit - Tailer, Kathleen (Love inspired suspense., 2019)
Evidence in their hands and a crime ring on their trail. Someone will do anything to get Mackenzie Weaver's documentary footage-even kill her. US deputy marshal Jake Riley won't let anyone harm Mackenzie, especially since he's beginning to see her as more than his late friend's little sister. But exploring their growing connection isn't an option because keeping an emotional distance is his best hope of outmaneuvering criminals determined to make this project Mackenzie's last.